CXCL12/CXCR4 axis governs Treg spatial dominance over CD8+ T cells via IL-2 sequestration: a dual therapeutic target in prostate cancer - Junyi Li; Long Zhang; Ruoyang Liu; Changwen Xu; HuiHui Tang; Yunfei Zou; Qingfei Cao; Weichao Huang (Frontiers in Immunology)
BackgroundProstate cancer (PCa) is characterized by high incidence and recurrence rates, presenting as an immune ‘cold’ tumor that exhibits a poor response to immunotherapy. The mechanisms underlying immune suppression and evasion within the tumor microenvironment (TME) of PCa remain inadequately understood.MethodsA comprehensive analysis of the immune environment in PCa was conducted using combined single-cell and spatial transcriptomic approaches, encompassing samples from healthy tissue, adjacent normal tissue, and localized tumors. Cell abundance and polarization state analyses were performed to identify pivotal cellular populations. Spatial deconvolution techniques were employed to elucidate cell composition within its spatial context. Additionally, cell niche and spatial colocalization analyses were conducted to evaluate potential cellular interactions. Immune response enrichment analysis was utilized to assess cellular response states. In vivo and in vitro experiments were conducted to validate hypotheses.ResultsData indicated a prevalent immunosuppressive state among CD8 T cells, accompanied by variations in cell abundance. Macrophages emerged as key regulators in recruiting CD8+ effector T cells and regulatory T cells (Tregs) into the TME, mediated by the CXCL12/CXCR4 axis. A spatial proximity relationship was established between CD8+ effector T cells and Tregs, suggesting Tregs directly influence CD8+ T cell function. Immune cell state analysis revealed interleukin-2 (IL-2) as a critical cytokine in reshaping the immune microenvironment, with Tregs competitively depleting IL-2 and mediating IL-2/STAT5 signaling to induce CD8+ effector T cell exhaustion. Treatment with CXCR4 inhibitor and IL-2 demonstrated significant antitumor effects and reversed immune dysfunction in both in vivo and in vitro experiments, with combined treatment exhibiting superior efficacy.ConclusionThese findings elucidate the role of macrophages in mediating the CXCL12/CXCR4 axis to aggregate CD8+ effector T cells and Tregs, thereby influencing the TME. Furthermore, Tregs competitively deplete IL-2 and mediate IL-2/STAT5 signaling, leading to CD8+ effector T cells exhaustion and the establishment of an immunosuppressive microenvironment.